Pregnancy-associated breast cancer: optimal treatment options - Cardonick E (Dove Medical Press, 2014)
Elyce Cardonick Division of Maternal-Fetal Medicine, Department of Obstetrics and Gynecology, Cooper University Hospital, Camden, NJ, USA Abstract: Cancer is diagnosed approximately once per 1,000 pregnancies; most commonly due to the reproductive age of the women, these include breast, cervical, melanoma, thyroid, and Hodgkin's lymphoma diagnoses. As a single diagnosis, breast cancer is the most common cancer diagnosed during pregnancy. Cancer is expected to complicate pregnancy more often due to the trend for women to delay child bearing to later maternal ages. Delayed first birth is itself a risk factor for breast cancer. Termination of pregnancy has not been shown to afford a survival benefit. While protecting the interests of mother and unborn fetus, breast cancer can be safely diagnosed, staged, and treated during pregnancy with good outcomes for both. Some modification of the protocols used for nonpregnant women with suspicious palpable breast masses is required. This article reviews the challenges for physicians in making the diagnosis of breast cancer during pregnancy and upon diagnosis, counseling patients about treatment options. The consequences of diagnostic investigations and cancer treatment for the exposed fetus are also addressed. Keywords: chemotherapy, in utero exposure, gestational